Risālah-i kašf al-asrār : tarjumah-i urdū mī bāyad šinīd - Rifʿat, Muḥammad ʿAlī (Naval Kišor, 1926)
Treatise on ethics and mysticism (akhlaq o tasavvuf) presented by means of Persian šiʿrs and Arabic quotations